Towards a User-Centred Systematic Review Service: The Transformative Power of Service Design Thinking. Issue 3 (2nd July 2020) - J. Luca, Edward; Ulyannikova, Yulia
ABSTRACT: The number of systematic reviews published each year has steadily increased over the past decade. At the University of Sydney Library, demand for systematic review support had reached unsustainable levels, and a reimagining of our service model was necessary. This paper documents our journey in using 'service design thinking' to develop a user-centred systematic review service. Using design thinking methods, we conducted user research to build empathy and understand the systematic review process from the user's perspective. Using the principles of service design, we examined systematic review support holistically and reconsidered library services as part of a wider service ecology. We developed a suite of resources, including a service charter and an online, self-service toolkit. We also launched a systematic review mentoring program to increase the number of librarians able to deliver the service. By bringing design thinking and service design together, we were able to examine an old problem from a new vantage point. Through this process we discovered the transformational power of service design thinking and developed new solutions for our local context. We encourage other libraries to also embrace service design thinking to reimagine their own services from a new perspective.